MENJAGA TRADISI CABLAKA DI ERA MILENIAL MELALUI COVER MAJALAH ANCAS BANYUMASAN - Bayu Aji Suseno; Luqman Wahyudi (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2020)
The publication of Ancas Banyumasan magazine is intended for market segmentation or target audience (consumers) of the millennial generation in the Barlingmascakep area (Banjarnegara, Purbalingga, Banyumas, Cilacap and Kebumen). The cover image of Ancas Banyumasan magazine presents a role model for local teenagers or young people who are not well known or less popular with an understated or simple (pose) style or attitude. The title of the main article of Ancas Banyumasan magazine uses Penginyongan language with persuasive sentences with provocative tones to maintain the character of the Cablaka culture which means speaking frankly or as is. This research uses a qualitative method with a descriptive analytic study approach, while data collection is by non-participant observation to obtain a picture or information on an objective state or certain event based on clear facts. The results of the study aimed to analyze the meaning of the cablaka concept in the cover design of Ancas Banyumasan magazine in building awareness of the millennial generation of the value of local wisdom. Penerbitan majalah Ancas Banyumasan ditujukan untuk segmentasi pasar atau target audience (konsumen) generasi milenial di wilayah Barlingmascakep (Banjarnegara, Purbalingga, Banyumas, Cilacap dan Kebumen). Image cover majalah Ancas Banyumasan menghadirkan role model remaja atau anak muda lokal yang tidak terkenal atau kurang popular dengan (pose) gaya atau sikap bersahaja atau sederhana. Judul artikel utama majalah Ancas Banyumasan menggunakan bahasa Penginyongan dengan kalimat persuasif bernada provokatif untuk mempertahankan karakter budaya cablaka yang berarti berbicara terus terang atau apa adanya. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi deskriptif analitik, sedangkan pengumpulan data dengan observasi non-partisipan untuk memperoleh gambaran atau informasi terhadap suatu keadaan objektif atau peristiwa tertentu berdasarkan fakta yang jelas. Hasil penelitian bertujuan untuk menganalisis makna konsep cablaka dalam desain cover majalah Ancas Banyumasan dalam membangun kesadaran (awareness) generasi milenial terhadap nilai kearifan lokal.Kata kunci : Cablaka, cover, majalah, ancas, banyumasan